Comparison of the effect of clarithromycin triple therapy with or without N-acetylcysteine in the eradication of Helicobacter pylori: a randomized controlled trial. (July 2020) - Chen, Chieh-Chang; Luo, Jiing-Chyuan; Fang, Yu-Jen; Lee, Ji-Yuh; Kuo, Chia-Chi; Yang, Tsung-Hua; Chiu, Min-Chin; Yu, Jian-Jyun; Bair, Ming-Jong; Chen, Po-Yueh; Chou, Chu-Kuang; Chen, Chi-Yi; et al.
Background: Whether adjunctive N -acetylcysteine (NAC) may improve the efficacy of triple therapy in the first-line treatment of Helicobacter pylori infection remains unknown. Our aim was to compare the efficacy of 14-day triple therapy with or without NAC for the first-line treatment of H. pylori . Material and methods: Between 1 January 2014 and 30 June 2018, 680 patients with H. pylori infection naïve to treatment were enrolled in this multicenter, open-label, randomized trial. Patients were randomly assigned to receive triple therapy with NAC [NAC-T14, dexlansoprazole 60 mg four times daily (q.d.); amoxicillin 1 g twice daily (b.i.d.), clarithromycin 500 mg b.i.d., NAC 600 mg b.i.d.] for 14 days, or triple therapy alone (T14, dexlansoprazole 60 mg q.d.; amoxicillin 1 g b.i.d., clarithromycin 500 mg b.i.d.) for 14 days. Our primary outcome was the eradication rates by intention to treat (ITT). Antibiotic resistance and CYP2C19 gene polymorphism were determined. Results: The ITT analysis demonstrated H. pylori eradication rates in NAC-T14 and T14 were 81.7% [276/338, 95% confidence interval (CI): 77.5–85.8%] and 84.3% (285/338, 95% CI 80.4–88.2%), respectively. In 646 participants who adhered to their assigned therapy, the eradication rates were 85.7% and 88.0% with NAC-T14 and T14 therapies, respectively. There were no differences in compliance or adverse effects. The eradication rates in subjects with clarithromycin-resistant, amoxicillin-resistant, or either clarithromycin/amoxicillin resistant strains were 45.2%, 57.9%, and 52.2%, respectively, for NAC-T14, and were 66.7%, 76.9%, and 70.0%, respectively, for T14. The efficacy of NAC-T14 and T14 was not affected by CYP2C19 polymorphism. Conclusion: Add-on NAC to triple therapy was not superior to triple therapy alone for first-line H. pylori eradication [ClinicalTrials.gov identifier: NCT02249546].